Hierarchical clustering-based framework for a posteriori exploration of pareto fronts : application on the bi-objective next release problem - Casanova Pietroboni, Carlos Antonio; Schab, Esteban Alejandro; Prado, Lucas Martín; Rottoli, Giovani Daian (Hector Florez, Universidad Distrital Francisco Jose de Caldas, Colombia., 2023)
When solving multi-objective combinatorial optimization problems using a search algorithm without a priori information, the result is a Pareto front. Selecting a solution from it is a laborious task if the number of solutions to be analyzed is large. This task would benefit from a systematic approach that facilitates the analysis, comparison and selection of a solution or a group of solutions based on the preferences of the decision makers. In the last decade, the research and development of algorithms for solving multi-objective combinatorial optimization problems has been growing steadily. In contrast, efforts in the a posteriori exploration of non-dominated solutions are still scarce.
Keywords: Search-based software engineering; Preference-based algorithms; Aposteriori approach; Hierarchical clustering; Multiobjective optimization; Pareto front